2017
DOI: 10.1177/1558944717743601
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Resection of Dorsal Wrist Ganglion: Results and Rate of Recurrence Over a Minimum Follow-up of 4 Years

Abstract: The outcomes, recurrence, and complications rates after 4 years of follow-up presented in this study support the use of arthroscopy as a treatment for dorsal wrist ganglion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 39 publications
3
24
0
11
Order By: Relevance
“…Likewise arthroscopic dorsal ganglion resection has been performed with satisfactory outcomes since it was first described by Osterman and Raphael (5). The results of our study showed that arthroscopic excision of dorsal wrist ganglions provides respectable clinical outcomes with elevated patient satisfaction, as reported in previous studies (9)(10)(11). The (12) reported that the pain decreased from 3.37 to 1.76 after arthroscopic resection.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise arthroscopic dorsal ganglion resection has been performed with satisfactory outcomes since it was first described by Osterman and Raphael (5). The results of our study showed that arthroscopic excision of dorsal wrist ganglions provides respectable clinical outcomes with elevated patient satisfaction, as reported in previous studies (9)(10)(11). The (12) reported that the pain decreased from 3.37 to 1.76 after arthroscopic resection.…”
Section: Discussionsupporting
confidence: 87%
“…Since rstly described by Osterman and Raphael in 1995 [15], the arthroscopic excision of DWG cysts has increased in popularity and showed inspiring results with a lower recurrence rate of approximately 10% [7][8][9][10][11]. In a study by Gallego and Mathoulin [10], a total of 114 patients underwent arthroscopic excisions of DWG cysts, and there were 14 (12.3%) recurrences at a mean of 16.9 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the arthroscopic DWG excision is becoming an alternative to open surgery for advantages in a smaller scar, less pain, and earlier return to work [3]. Meanwhile, the recurrence following arthroscopic DWG excision was reported to be approximately 10% at > 1-year follow-up [7][8][9][10][11], indicating the possible superiority of arthroscopic approach in lowing the recurrence of DWG. However, in patients with recurrent DWG, it is unclear whether a re-excision under arthroscopy would achieve a low recurrence as the primary surgery.…”
mentioning
confidence: 99%
“…Neben einer dorsalen Synovialektomie wird der dorsale Ganglienstiel auf einen Kapseldefekt von 10 × 10 mm erweitert, um den Ventilmechanismus zu beseitigen. Die Rezidivrate beträgt zwischen 3 und 30 % und entspricht damit der offener Verfahren [4]. gelenk darf sofort bewegt werden.…”
Section: Operationen Von Ganglienunclassified
“…Auch die Teilresektion des triangulären fibrokartilaginären Komplexes (TFCC) wurde relativ frühzeitig in die Therapie integriert. Im Verlauf kamen die arthroskopische Therapie von Handgelenkganglien [4,5] sowie geschlossene, rein arthroskopische oder arthroskopisch assistierte minimalinvasive Verfahren zur Refixation des TFCC nach traumatischen Rupturen zur Anwendung Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen. Vervielfältigung nur mit Zustimmung des Verlages.…”
Section: Introductionunclassified